Speciation and zoogeography of amphibian in Sundaland - Nia Kurniawan; Driyana Rike Ahmadlia; Day Shine Nahari; Anggun Sausan Firdaus (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2015)
Sundaland is an interesting area to be explored based on its geological history, topography, and climate. Sundaland consists of Penisular Malaysia, Sumatra, Borneo, and Java which experienced some emergence and submergence process in the past. During 1981-2015, most of research in Sundaland found that amphibian family in Sundaland was dominated by Bufonidae, Ranidae, Microhylidae, Megophrydae, Rachophoridae, and Dicroglossidae which experienced lot of speciation in its history. Among of 4 major islands in Sundaland, Borneo has the highest number of species diversity, then Peninsular Malaysia, Sumatra, and Java. During those years, Sumatra and Java got least concern by researcher. Therefore, it is suggested for further study to explore more in Sumatra and Java.